Recent Advances in Modeling Mitochondrial Cardiomyopathy Using Human Induced Pluripotent Stem Cells - Pavez-Giani, Mario G.; Cyganek, Lukas (Frontiers in Cell and Developmental Biology, 2022)
Around one third of patients with mitochondrial disorders develop a kind of cardiomyopathy. In these cases, severity is quite variable ranging from asymptomatic status to severe manifestations including heart failure, arrhythmias, and sudden cardiac death. ATP is primarily generated in the mitochondria respiratory chain via oxidative phosphorylation by utilizing fatty acids and carbohydrates. Genes in both the nuclear and the mitochondrial DNA encode components of this metabolic route and, although mutations in these genes are extremely rare, the risk to develop cardiac symptoms is significantly higher in these patients cohort. Additionally, infants with cardiovascular compromise in mitochondrial deficiency display a worse late survival compared to patients without cardiac symptoms. At this point, the mechanisms behind cardiac disease progression related to mitochondrial gene mutations are poorly understood and current therapies are unable to substantially restore the cardiac performance and to reduce the disease burden. Therefore, new strategies are needed to uncover the pathophysiological mechanisms and to identify new therapeutic options for mitochondrial cardiomyopathies. Here, human induced pluripotent stem cell (iPSC) technology has emerged to provide a suitable patient-specific model system by recapitulating major characteristics of the disease in vitro, as well as to offer a powerful platform for pre-clinical drug development and for the testing of novel therapeutic options. In the present review, we summarize recent advances in iPSC-based disease modeling of mitochondrial cardiomyopathies and explore the patho-mechanistic insights as well as new therapeutic approaches that were uncovered with this experimental platform. Further, we discuss the challenges and limitations of this technology and provide an overview of the latest techniques to promote metabolic and functional maturation of iPSC-derived cardiomyocytes that might be necessary for modeling of mitochondrial disorders.